2022
DOI: 10.1002/uog.24917
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spontaneous preterm birth and preterm prelabor rupture of membranes using maternal factors, obstetric history and biomarkers of placental function at 11–13 weeks

Abstract: What are the novel findings of this work?We have demonstrated that first-trimester maternal serum pregnancy-associated plasma protein-A (PAPP-A) and placental growth factor (PlGF) levels are reduced in cases of spontaneous preterm birth (sPTB) and preterm prelabor rupture of membranes (PPROM) at < 37 weeks, suggesting that placental insufficiency is implicated in the underlying pathophysiology of these complications. What are the clinical implications of this work?In addition to increased risks of fetal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…9 Angiogenic imbalance represents one of the underlying pathologies of PPROM. 28 The angiogenic imbalance in the maternal circulation of women who later develop PPROM can be observed even in the first trimester of the pregnancy 32 and is further pronounced in the second and third trimesters of pregnancy. 8 Romero et al have recently shown that the earliest gestational age at which concentrations of PlGF, sFlt-1 and their ratio become different from uncomplicated pregnancy are gestational ages 30, 31 and 27 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…9 Angiogenic imbalance represents one of the underlying pathologies of PPROM. 28 The angiogenic imbalance in the maternal circulation of women who later develop PPROM can be observed even in the first trimester of the pregnancy 32 and is further pronounced in the second and third trimesters of pregnancy. 8 Romero et al have recently shown that the earliest gestational age at which concentrations of PlGF, sFlt-1 and their ratio become different from uncomplicated pregnancy are gestational ages 30, 31 and 27 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study of 11 437 women undergoing first‐trimester screening for preterm pre‐eclampsia by a combination of maternal risk factors, MAP, UtA‐PI and PAPP‐A, reported that in those with estimated risk of ≥1 in 50, compared with those with a risk <1 in 50, the odds ratio for iPTB was 6.0 (95% CI 4.29–8.43) and that for sPTB was 2.0 (95% CI 1.46–2.86) 11 . Another study of 9298 singleton pregnancies reported that first‐trimester biomarkers of placental function can be used to screen for sPTB; inclusion of PlGF and PAPP‐A improved the DR of sPTB at <37 weeks of gestation provided by maternal risk factors from 17% to 25%, at FPR of 10% 12 …”
Section: Discussionmentioning
confidence: 99%
“…11 Another study of 9298 singleton pregnancies reported that first-trimester biomarkers of placental function can be used to screen for sPTB; inclusion of PlGF and PAPP-A improved the DR of sPTB at <37 weeks of gestation provided by maternal risk factors from 17% to 25%, at FPR of 10%. 12 A Swedish register-based cohort study investigated the association between low-dose aspirin use and PTB among 22 127 women with a previous PTB and concluded that low-dose aspirin use was associated with a reduced risk for sPTB (relative risk [RR] 0.70; 95% CI 0.57-0.86) but had no significant effect on iPTB (RR 1.09; 95% CI 0.91-1.30). 13 A double-blind, placebo-controlled trial of low-dose aspirin (81 mg daily) versus placebo from 6 to 13 weeks of gestation until 36 weeks in 11 976 nulliparous women with singleton pregnancies found that aspirin was associated with an 11% reduction in the risk of PTB at <37 weeks of gestation (RR 0.89, 95% CI 0.81-0.98) but the study did not provide data as to whether the PTB was spontaneous or iatrogenic and whether there was any association with pre-eclampsia.…”
Section: Outcome Measurementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is used to predict the need for delivery within 14 days, with a sensitivity (the ability of the test to identify true positives) and specificity (the ability of the test to identify true negatives) of 80% for both and positive and negative predictive values (the proportion of individuals with a positive test result who will deliver preterm or with a negative test result who will not deliver preterm) of 0.41 and 0.95, respectively (using the Triage MeterPro point-of-care analyzer that uses a fluorescence immunoassay) [57]. More recently, PLGF has been investigated as a potential biomarker for predicting spontaneous PTL, and this is discussed later in this review [58]. Prediction and prevention rely on identifying high-risk patients using their medical and obstetric history to determine risk factors.…”
Section: Current Clinical Tools To Predict Preterm Birthmentioning
confidence: 99%